Effect of NaOH concentration on production of Na-CMC derived from pineapple waste collected from local society - Faridah Anni; Azhar Aulia; Suryanto Heru; Saputra Ilman; Utami Oktria Putri; Kasmita; Makky Muhammad; Syukri Daimon (Open Agriculture)
This study was conducted to observe the characteristics of sodium carboxymethyl cellulose (Na-CMC) made from bacterial cellulose from pineapple peel waste obtained from the results of community business activities. Na-CMC was made from pineapple peel waste cellulose with various sodium hydroxide concentration treatments. The alkalization process with NaOH is critical to start the carboxymethylation process to produce CMC. Na-CMC was manufactured with various NaOH concentrations in the range of 5, 7.5, 10, 12.5, and 15%. The resulting Na-CMC was then analyzed for quality using several parameters such as water content, NaCl content, Na-CMC purity, and degree of substitution (DS). The application of Na-CMC was tested in the view of viscosity and pH. As a result, it can be reported that the concentration of NaOH dramatically affects the character of the resulting Na-CMC. The NaOH concentration of 10% produced the best Na-CMC in this study, with the highest purity and DS value. As information for the application of the Na-CMC produced, the Na-CMC produced was measured for the pH value and viscosity. As a result, it can be reported that the pH of the Na-CMC solution was categorized as neutral, and the viscosity value was directly proportional to the purity of Na-CMC. The findings of this study have provided information on the potential of pineapple peel waste to produce Na-CMC, even though the material was not standardized because it comes from annual public activity.